Membrane separator for alkaline water electrolysis
Patent Information
- Application Number
- JP2025531037
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-30
- Filing Date
- 2023-11-28
- Publication Date
- 2026-10-14
AI Technical Summary
Existing alkaline water electrolysis separators face challenges such as high cross-permeation resistance, low ionic conductivity, and operational difficulties due to the need for humid storage, which are exacerbated by the ban on asbestos and limitations of synthetic membranes.
A symmetric separator membrane is developed using a double-sided casting method with a thermoplastic polymer and inorganic filler, allowing for dry storage and improved ionic conductivity, gas separation, and resistance to oxidative degradation, featuring uniform pore distribution and symmetrical structure.
The membrane achieves high ionic conductivity, low ohmic resistance, and effective gas separation, with reduced bacterial contamination risk and oxidative stability, enabling efficient hydrogen production without humid storage requirements.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] In order to prevent global warming, many carbon dioxide emission reduction projects are underway around the world. [Background technology]
[0002] For many years, renewable or "zero carbon" energy alternatives have been discussed as a sustainable alternative to conventional hydrogen production. From mobility to renewable energy storage, this research aims to make green hydrogen a concrete option for reducing emissions.
[0003] Green hydrogen has attracted international attention with the aim of achieving decarbonization and energy transition goals. In addition to meeting the threshold requirements of low carbon emissions, green hydrogen can also be produced using renewable energy sources such as solar, wind, or hydroelectric energy sources.
[0004] In the latter activity, fuel cells are used in various applications, such as automobiles and power supply systems. Today, the most common industrial hydrogen production process is the steam reforming process. However, this process uses fossil gas as a resource and has the problem of emitting carbon dioxide and other pollutants. Therefore, alkaline water electrolysis, which is powered by renewable energy, has attracted worldwide attention as a hydrogen supply method that does not also emit carbon dioxide.
[0005] In the alkaline water electrolysis process, an alkaline electrolyte enters the anode and cathode regions on either side of a membrane, allowing water molecules to pass through the membrane to the other side. An electric current causes water molecules in the electrolyte in the cathode region to combine with electrons to form hydrogen molecules and hydroxide ions. Additionally, in the anode region, the hydroxide ions lose electrons to produce oxygen and water. Because of the obstruction of the permeable membrane, gases produced by electrolysis cannot pass through the separator to the other side, and both the produced gases and the electrolyte are discharged from the chamber for disposal.
[0006] In alkaline water electrolysis systems, one of the important materials that affects the efficiency of hydrogen production is the diaphragm or separator.
[0007] The separator for alkaline water electrolysis is High resistance to cross-permeation of hydrogen and oxygen, and Requires high ionic conductivity, resulting in low ohmic resistance.
[0008] Furthermore, because alkaline water electrolysis operates under extremely harsh conditions, such as high temperatures and high alkaline concentrations, there were very few separators that could be used for alkaline water electrolysis. Conventional separators were often made from asbestos mesh. This material is now banned in most countries around the world, requiring the manufacture of separators that do not contain this carcinogenic compound.
[0009] The choice shifted to synthetic separators consisting of supported polymer membranes.
[0010] Various types of such separator membranes are already commercially available.
[0011] Although these separator membranes have excellent properties in terms of ionic resistance and resistance to oxidizing environments, they have the disadvantage that they must be stored in a humid environment (see, for example, EP 3933069 A1), which entails additional costs for transportation and storage, as well as greater operational difficulties for separator users. Summary of the Invention
[0012] Advantageously and unexpectedly, the separator membranes obtained by the process of the present invention overcome the shortcomings of prior art products and can be stored in a dry, water-free state. Advantageously, the separator membranes of the present invention can be stored in such conditions due to the process by which they are obtained, which process does not generally stipulate the use of water.
[0013] The fact that it can be stored without water also has the advantage of minimizing the risk of bacterial / fungal contamination of the separator membrane.
[0014] Furthermore, the separator membrane obtained by the process of the present invention has further advantages over the prior art products available on the market. In fact, the separator membrane obtained by the process of the present invention provides a material with a double lining, a symmetrical surface structure, and a uniform porosity. This has the following characteristics over the prior art: Electrolytic absorption Ohmic resistance Ionic conductivity, and Leads to improved effective gas separation.
[0015] The present invention will be described in detail below.
[0016] Definition - Method hydrophilic The expression "hydrophilic" film is used to denote a film in which the contact angle between the liquid (eg, a drop of water) and the surface of the polymer forming the film is less than 90°.
[0017] Macroporous According to the TUPAC (International Union of Pure and Applied Chemistry) classification, a membrane is considered macroporous if it has pores larger than 50 nm in diameter (Mulder et al., "Basic Principles of Membrane Technology", Kluwer Academic Publishers, Dordrecht, 2nd Edition, p. 159, 1996). In advanced porometry measurements, the pore sizes of the membranes measured range from 0.1 to 5.23 μm.
[0018] Isotropic / Anisotropic Isotropic / symmetric membranes "have a perfectly uniform composition and structure, i.e., such membranes can be porous or dense. Instead, anisotropic (or asymmetric) membranes are composed of multiple layers, each with different structure and permeability. A typical anisotropic membrane has a relatively dense, thin surface layer supported on an open, much thicker, microporous substrate.' (Baker et al., "Membrane Technology and Application", Wiley and Sons, 3rd edition, 2012)
[0019] BP This refers to the point at which gas flow can be observed, indicating that the pressure is high enough to expel liquid from the largest pores. The pressure at which a steady stream of bubbles appears in this test is the bubble point pressure (ASTM F316 - 03; Standard test methods for pore size characteristics of membrane filters by bubble point and mean flow pore test).
[0020] Pore size distribution / average pore size Advanced dehumidification of the pores by perm-porometry with gas / liquids can provide information on various parameters for measuring pore size.
[0021] The pore size can be defined in practice as "at the bubble point" and "on average" (Dapeng, et al., "Characterization of nanofibrous membranes with capillar flow porometry", Journal of Membrane Science, Elsevier, Volume 286, Issues 1-2, pages 104-114, 2006; M. Khayet and T. Matsuura "Membrane Distillation: Principles and Applications" Elsevier 2011, Chapter 8 - Membrane characterization MD).
[0022] To measure pore size parameters, the membranes of the present invention were subjected to a wet-up / dry-down porometry measurement method using a certified advanced capillary flow porometer (obtained from PMI). In this method, a fixed area of membrane is first immersed in a suitable wetting liquid and subjected to steadily increasing gas pressures. For each applied gas pressure, the gas flow rate is measured. The point at which gas flow can be measured indicates that the pressure is high enough to expel liquid from the largest pores (the bubble point pressure). This pressure is used to define the maximum pore size and is known as the pressure "at the bubble point." Further increases in pressure expel liquid from even the smallest pores, increasing the flow rate until all pores are empty.
[0023] In the second part of the characterization, the gas flow is measured as a function of pressure through the dry membrane. The point at which the flow rate through the wet sample is the same as the flow rate through the dry sample is the smallest pore size. The mean pore size "at mean flow rate" is determined at 50% of the "wet flow" (wet measurement) versus the gas flow through the dry membrane (dry down) at the same pressure.
[0024] Membranes prepared using the method of the present invention have pore sizes between 0.1 μm and 5.2 μm at average flow rates. By comparing the dry and wet flow rates at each pressure (corresponding to a particular porosity according to Laplace's equation), the pore size distribution can be determined.
[0025] Ohmic Resistance / Ionic Conductivity For membrane resistance measurements, a linear voltage sweep (potential-dynamic scan) is commonly used. The voltage sweep results in a straight line plotted as voltage (V) versus current (A), with the slope representing the resistance (Q) (voltage sweep shown in Figure 3).
[0026] To determine the calculated film and conductivity resistance, use the resistance R cell This resistance to the test environment of interest can be determined by assembling the cell without the sample under test. R cell is a function of the conductivity of the solution in question.
number
number
[0027] Oxidation resistance Chemical stability in alkaline oxidation is an important property for the practical use of the membrane of the present invention. The oxidation stability of the sample of the present invention and the comparative sample was estimated by observing the weight loss of the membrane using Fenton's reagent.
[0028] Fenton's reagent generates free radicals, which can lead to significant degradation of the membrane. The oxidative stability of AWE membranes was investigated by adding 50 ppm Fe. 2+ This was achieved at room temperature in 5% H2O2, pH = 3. Gradual weight loss of the membrane was observed over time after 72 hours. It was also possible to analyze whether the membrane cracked or dissolved. (Method based on the article by Zhanga et al. "Development of a high-performance anion exchange membrane using poly(isatin biphenylene) with flexible heterocyclic quaternary ammonium cations for alkaline fuel cells," Journal of Materials Chemistry A, Issue 12, 2019 (internally validated).)
[0029] Scanning electron microscope (SEM) Scanning electron microscopy (SEM) can be used to directly visualize the morphology of the membrane. The top and bottom surfaces of the membranes according to the invention were examined.
[0030] Double-sided casting method This is a commonly used process known to those skilled in the art and can be carried out vertically or horizontally using a doctor blade, a die coater, or by immersion spraying onto a double blade knife, after which the sprayed solution is immersed in a coagulation bath where an inversion step is carried out.
[0031] Opening area Open area is the total area of the openings divided by the total area of the material, expressed as a percentage. [Brief explanation of the drawings]
[0032] [Figure 1]Figure 1 (1.1, 1.2, 1.3, and 1.4) are images of both sides (designated "top" and "bottom") obtained using SEM of two samples of separator membranes obtained with the process of the present invention (symmetrical GVS1 and GVS4). [Figure 2] Figure 2 (2.1 and 2.2) are images of both sides (labeled "top" and "bottom") obtained using SEM of a sample of one of the commercially available separator membranes. [Figure 3] FIG. 3 is a voltage sweep diagram. [Figure 4] Figure 4 shows the results of a simulation test on the aging and degradation of the membrane that is the subject of the present invention, in which a sample of the present invention (GVS) was considered and compared with a currently available commercially available sample (Competitor 3). DETAILED DESCRIPTION OF THE INVENTION
[0033] The present invention will be described in detail below.
[0034] In one embodiment, the present invention provides a symmetric separator membrane for alkaline water electrolysis having a uniform pore distribution, comprising: a) dissolving a thermoplastic polymer in a dispersion liquid comprising an inorganic filler and an organic solvent, the thermoplastic polymer is selected from the group consisting of polysulfone (PSU), polyethersulfone, polyphenylsulfide, polyetheretherketone (PEEK), polyurethane (PU), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinyl acetate (PVAc); the inorganic filler is selected from the group consisting of zirconium oxide, zirconium hydroxide, yttrium-doped zirconium oxide, magnesium oxide, magnesium hydroxide, titanium oxide, titanium hydroxide, and barium sulfate; the organic solvent is selected from the group consisting of dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO); The components are present in the following ranges: Thermoplastic polymers 7-18% (wt / wt), Inorganic fillers are 20-35% (wt / wt), and Organic solvents are present in the range of 48-72% (wt / wt), the sum of the ingredients equals 100% (wt / wt); b) degassing the solution obtained in step a); c) applying the solution obtained in step b) to a centrally placed permeable medium by the "double-sided casting" technique in a coagulation bath to form a membrane, the permeable medium is selected from the group consisting of paraphenylene sulfide (PPS), polypropylene, polyethylene, and polyetheretherketone (PEEK); The coagulation bath consists of a solvent and an alcohol, the solvent is selected from the group consisting of dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO); the alcohol is selected from the group consisting of ethyl alcohol, isopropyl alcohol, and methyl alcohol; d) washing the membrane obtained in step c) with alcohol; e) drying the membrane obtained in step d), The resistance per specific area of this separator membrane is 0.03 to 0.3 Ω cm when measured at room temperature and with a 30% KOH concentration. 2 This relates to a separator membrane that is in the range of
[0035] Preferably, the separator membrane can be stored in a dry environment without degradation of its mechanical properties and electrochemical performance.
[0036] Preferably, the inorganic filler in step a) is selected from the group consisting of zirconium oxide, yttrium-doped zirconium oxide.
[0037] Preferably, the permeable medium in step c) is paraphenylene sulfide having a thickness of 60 to 450 μm and an open area of 40 to 60%.
[0038] Preferably, the permeable medium is a "woven" type permeable medium.
[0039] Preferably, the pore size of the present separator membrane is in the range of 0.1 to 5.2 μm (according to the WET-UP / DRY-DOWN method).
[0040] Preferably, the Fenton reaction (pH = 3, 5% H2O2, 50 ppm Fe 2+ The weight loss of the separator membrane in the oxidation stability test by ) during the first 96 hours is in the range of 3-5%.
[0041] Preferably, before use, the thermoplastic polymer is placed in an oven overnight (8 hours) to remove any moisture already present that may have been absorbed during storage (standard laboratory practice).
[0042] Preferably, in the dispersion of zirconium oxide (ZrO2) in the solvent of step a), all of the ZrO2 and some of the DMAc are used to concentrate the filler weight percentage to 42% during the dispersion step. Specifically, a ZrO2 / DMA weight ratio of 42 / 58 is used. The remaining DMA is added after the dispersion step to achieve the final % of Zr in solution.
[0043] Preferably, the dispersion in step a) is carried out according to techniques known to those skilled in the art, for example using a ball mill, rotor / stator, high shear mixer, etc.
[0044] Preferably, the dissolution in step a) is carried out by stirring the solution for a period of 2 to 8 hours, preferably 6 hours. The solution is considered "complete" when the entire PSU has dissolved and a uniform white dispersion has formed.
[0045] Preferably, the degassing in step b) is carried out over a period of 0.5 to 3 hours, preferably 1 hour.
[0046] Such a degassing step allows the solution to stand and allow air bubbles to escape from the solution, avoiding defects that may occur during deposition onto the medium.
[0047] Preferably, the permeable medium of step c) has a thickness in the range of 60 to 450 μm.
[0048] Preferably, the temperature of the coagulation bath is room temperature (RT, 25° C.).
[0049] The "double-sided casting" technique allows obtaining a membrane that is symmetrical on both sides, i.e. a product with polymer on both sides and the medium in the middle. This technique specifies the use of NIPS (non-solvent induced phase separation). In this method, a liquid solution is transformed into a membrane in the solid state by de-mixing, a process in which the solvent in the solution moves into a coagulation bath, while the non-solvent moves from the coagulation bath into the solution.
[0050] Preferably, the residence time in the coagulation bath in step c) is in the range of 5 to 15 minutes.
[0051] Preferably, the washing of the separator membrane in step d) is carried out over a period of 5 to 15 minutes.
[0052] Preferably, this cleaning is carried out under static or dynamic conditions.
[0053] Preferably, the drying in step e) is carried out at a temperature of 50 to 100° C., preferably 80° C., for a period of 5 to 10 minutes, preferably 5 to 7 minutes.
[0054] Advantageously, the separator membrane of the present invention can be stored free of water, particularly since the process for its implementation advantageously does not provide for the use of water.
[0055] The separator membranes of the present invention were characterized by the following techniques: SEM, feeler gauge, porometry, BP, electroabsorption, H-cell (ohmic resistance is measured, from which ionic conductivity and area resistance are derived), solution density, and oxidation stability.
[0056] Advantageously, the separator membrane obtained by the process of the present invention can ensure pure gas production due to uniform pore distribution.
[0057] Advantageously, the separator membrane obtained by the process of the present invention exhibits high electrolyte retention capacity due to the symmetrical morphology of the surface and spongy interior of the product.
[0058] Advantageously, the separator membrane of the present invention has high ionic conductivity and low ohmic resistance due to the uniform distribution of nanoparticles less than 40 nm in diameter.
[0059] Advantageously, the separator membrane of the present invention can be stored dry, eliminating all of the problems associated with products stored wet.
[0060] Advantageously, the separator membrane of the present invention exhibits high resistance to oxidative degradation, experiencing less than 5% weight loss in highly oxidative environments.
[0061] Advantageously, the process presented in this invention can avoid the use of water in all steps for preparing the separator membrane, and the amount of inorganic filler used is reduced compared to the state of the art due to its size on the nanometer scale.
[0062] Below are presented some non-limiting and illustrative experiments aimed at better illustrating the technical aspects and advantages of the present invention.
[0063] Example The ZrO2 used in the experiments was manufactured by Inframat Advanced Materials and had a diameter of 20-30 nm and a purity of 99.9+%.
[0064] The polysulfone used in the experiments of the present invention is manufactured by Solvay.
[0065] Example 1 A symmetric membrane according to the invention is prepared from a solid:liquid weight ratio of 1:1.5, with an inorganic:polymer ratio of 3:1.
[0066] The solid part consists of a chemically resistant polymer, a type of polysulfone (PSU or PES), and an inorganic filler made of zirconium oxide.
[0067] The resulting membrane can range in thickness from 190 to 450 μm and is reinforced with a porous medium made of PPS.
[0068] The resulting membranes have ionic resistance properties at least comparable to those of currently available commercially available membranes, with the advantage that they can be stored and used in a dry, rather than wet, state.
[0069] The difference between Sample 1 and Sample 3 of the present invention is the type of polymer (PSU vs. PES), and the difference between Sample 1 and Sample 2 is the cast thickness. Three samples of currently available products were also analyzed. These three samples are hereinafter referred to as Competitive Product 1, Competitive Product 2, and Competitive Product 3, and their main characteristics are listed below. [Table 1]
[0070] [Table 2]
[0071] Example 2 A symmetric membrane according to the invention is prepared from a solid:liquid weight ratio of 1:1.5, with an inorganic:polymer ratio of 3:1.
[0072] The solid portion consists of a chemically resistant polymer, a type of polysulfone, and an inorganic filler made of zirconium oxide.
[0073] The resulting membrane can range in thickness from 190 to 450 μm and is reinforced with a porous medium made of PPS.
[0074] The films of the present invention also exhibit greater resistance in oxidizing environments.
[0075] This test is used to simulate membrane aging and degradation.
[0076] This test shows the loss of weight over time.
[0077] In this study, a sample of the present invention (GVS) was considered and compared to a currently available commercially available sample (Competitor 3 as defined above). The results are shown in FIG.
[0078] Example 3 The membranes according to the invention are prepared from a solid:liquid weight ratio of 1:1.5, with an inorganic:polymer ratio of 3:1.
[0079] The solid portion consists of a chemically resistant polymer, a type of polysulfone, and an inorganic filler made of zirconium oxide.
[0080] The resulting membrane can range in thickness from 190 to 450 μm and is reinforced with a porous medium made of PPS.
[0081] The table below shows the difference in properties of the formulation of the present invention (as described in Example 1) when varying the phase separation technique.
[0082] Specifically, new membranes were obtained using NIPS or VIPS+NIPS. [Table 3]
[0083] Example 4 The symmetric membranes of the present invention are prepared from a 1:1.5 weight ratio of solid to liquid, resulting in a 3:1 inorganic to polymer ratio. The solid portion consists of a chemically resistant polymer, a polysulfone, and an inorganic filler made of zirconium oxide. The resulting membranes can range in thickness from 190 to 450 μm and are reinforced with a porous medium made of PPS.
[0084] The inorganic fillers used in the novel membranes of the present invention may also contain % yttrium oxide.
[0085] The table below shows the resistance values obtained with the new fillers: The only difference between the inventive sample GVS1 (described in Example 1) and GVS4 is the type of inorganic filler, specifically whether this filler is pure zirconia or yttrium-doped zirconia. [Table 4]
[0086] Example 5 A symmetric membrane according to the invention is prepared from a solid:liquid weight ratio of 1:1.5, with an inorganic:polymer ratio of 3:1.
[0087] The solid portion consists of a chemically resistant polymer, a type of polysulfone, and an inorganic filler made of zirconium oxide.
[0088] The resulting membrane can range in thickness from 190 to 450 μm and is reinforced with a porous medium made of PPS.
[0089] The membrane of the present invention is obtained by spraying the same solution on both sides, resulting in a symmetrical membrane.
[0090] By obtaining a membrane that is symmetrical and porous on both sides, many properties such as electroabsorption, ohmic resistance, and ionic conductivity are improved.
[0091] 1 and 2 show images obtained with a scanning electron microscope (SEM) of two symmetric membranes of the invention (GVS1 and GVS4).
[0092] Example 6 The membranes according to the invention are prepared from a solid:liquid weight ratio of 1:1.5, with an inorganic:polymer ratio of 3:1.
[0093] The solid portion consists of a chemically resistant polymer, which is a type of polysulfone, and an inorganic filler consisting of stabilized or unstabilized zirconium oxide.
[0094] The resulting membrane can range in thickness from 190 to 450 μm and is reinforced with a porous medium made of PPS.
[0095] The table below considers prototypes with thicknesses in the range of 190-250 μm and shows the electroabsorption values compared to competitive products in the same thickness range. [Table 5]
Claims
1. A symmetrical separator membrane for alkaline water electrolysis having a uniform pore distribution, wherein the following: a) A step of dissolving a thermoplastic polymer in a dispersion consisting of an inorganic filler and an organic solvent, The thermoplastic polymer is selected from the group consisting of polysulfone, polyethersulfone, polyphenyl sulfide, polyetheretherketone, polyurethane, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, and polyvinyl acetate. The inorganic filler is selected from the group consisting of zirconium oxide, zirconium hydroxide, yttrium-doped zirconium oxide, magnesium oxide, magnesium hydroxide, titanium oxide, titanium hydroxide, and barium sulfate. The aforementioned organic solvent is selected from the group consisting of dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, N-butylpyrrolidone, dimethylformamide, and dimethyl sulfoxide. The aforementioned components exist within the following ranges, namely, Thermoplastic polymers are 7-18% (by weight / by weight). The inorganic filler is 20-35% (by weight), and The aforementioned organic solvent is present in a range of 48-72% (by weight / weight), The sum of the above components is equal to 100% (weight / weight), in the process, b) A step of degassing the solution obtained in step a), c) A step of creating a film by applying the solution obtained in step b) to a permeable medium placed in the center using a "double-sided casting" technique in a solidification bath, The permeable medium is selected from the group consisting of paraphenylene sulfide, polypropylene, polyethylene, and polyether ether ketone. The aforementioned coagulation bath consists of a solvent and an alcohol. The solvent is selected from the group consisting of dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, N-butylpyrrolidone, dimethylformamide, and dimethyl sulfoxide. The alcohol is selected from the group consisting of ethyl alcohol, isopropyl alcohol, and methyl alcohol, and the process is as follows: d) A step of washing the film obtained in step c) with alcohol, e) A separator film obtained by drying the film obtained in step d), The resistance per specific area of the separator film was measured at room temperature and a KOH concentration of 30%, and was found to be 0.03 to 0.3 Ω·cm. 2 A separator film within that range.
2. The separator film according to claim 1, wherein the separator film is stored in a dry environment without degrading its mechanical properties and electrochemical performance.
3. The separator film according to claim 1 or 2, wherein the inorganic filler in step a) is selected from the group consisting of zirconium oxide and yttrium-doped zirconium oxide.
4. The separator film according to claim 1 or 2, wherein the permeable medium in step c) is paraphenylene sulfide having a thickness of 60 to 450 μm and an aperture area of 40 to 60%.
5. The separator membrane according to claim 1 or 2, wherein the pore diameter of the separator membrane is in the range of 0.1 to 5.2 μm (according to the wet-up / dry-down method).
6. Fenton reaction (pH = 3.5% H 2 O 2 , 50 ppm Fe 2+ The separator membrane according to claim 1 or 2, wherein the weight loss of the separator membrane in the oxidation stability test during the first 96 hours is in the range of 3 to 5%.